ANALISIS KADAR ALKALOID DAN FLAVONOID SEDUHAN RAMBUT JAGUNG (Zea mays L. ) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Al Azzahra, Yunita; Hidayat, Taufik Septiyan; Dewi, Lisna; Saepudin, Syumillah; Kartikawati, Endah; Rahayu, Iseu; Ajeng, Nurtina Dwi; Widiyaningrum, Eva Mutba (Jurnal Buana Farma, 2024)
Corn silk is generally a waste of sweet corn plants after being harvested and is rarely used, however, on the other hand, corn silk is also used by the community as herbal medicine and is believed to reduce the risk of hypertension and other types of chronic diseases such as kidney infections. Corn silk is thought to contain metabolite compounds such as flavonoids, essential oils, steroids, and alkaloids. Alkaloid compounds can function as drugs and strong activators for immune cells that can destroy bacteria, viruses, fungi, and cancer cells. Flavonoid compounds are compounds that have various bioactive effects such as anti-inflammatory, antiviral, cardioprotective, anti-diabetic, anti-cancer, anti-aging, and antioxidants. it is necessary to measure the levels of alkaloids and flavonoids from corn silk infusion to determine the levels of alkaloid and flavonoid compounds in corn silk infusion. The method used in this study is the Uv-Vis spectrophotometry method. The alkaloid content was calculated using the regression formula y = 0.0895x - 0.3046, the results obtained in the corn hair infusion extract were 46.36 mg / g extract, and the flavonoid content was calculated using the regression formula y = 0.0144 x - 0.025 and the results obtained in the corn hair infusion extract were 85.42 mg / g extract. So it can be concluded that corn hair infusion contains more flavonoid compounds, namely with alkaloid compound levels of 46.36 mg / g extract and flavonoid compounds of 85.42 mg / g extract.